Methanotrophic activity and diversity in different Sphagnum magellanicum dominated habitats in the southernmost peat bogs of Patagonia - Kip, N. (2012)
Sphagnum peatlands are important ecosystems in the methane cycle. Methanotrophs living inside the dead hyaline cells or on the Sphagnum mosses are able to act as a methane filter and thereby reduce methane emissions. We investigated in situ methane concentrations and the corresponding activity and diversity of methanotrophs in different Sphagnum dominated bog microhabitats. In contrast to the Northern Hemisphere peat ecosystems the temperate South American peat bogs are dominated by one moss species; Sphagnum magellanicum. This permitted a species-independent comparison of the different bog microhabitats. Potential methane oxidizing activity was found in all Sphagnum mosses sampled and a positive correlation was found between activity and in situ methane concentrations. Substantial methane oxidation activity (23 μmol CH 4 gDW -1 day -1) was found in pool mosses and could be correlated with higher in situ methane concentrations (>35 μmol CH 4 l -1 pore water). Little methanotrophic activity (<0.5 μmol CH 4 gDW -1 day -1) was observed in living Sphagnum mosses from lawns and hummocks. Methane oxidation activity was relatively high (>4 μmol CH 4 gDW -1 day -1) in Sphagnum litter at depths around the water levels and rich in methane. The total bacterial community was studied using 16S rRNA gene sequencing and the methanotrophic communities were studied using a pmoA microarray and a complementary pmoA clone library. The methanotrophic diversity was similar in the different habitats of this study and comparable to the methanotrophic diversity found in peat mosses from the Northern Hemisphere. The pmoA microarray data indicated that both alpha- and gammaproteobacterial methanotrophs were present in all Sphagnum mosses, even in those mosses with a low initial methane oxidation activity. Prolonged incubation of Sphagnum mosses from lawn and hummock with methane revealed that the methanotrophic community present was viable and showed an increased activity within 15 days. The high abundance of methanotrophic Methylocystis species in the most active mosses suggests that these might be responsible for the bulk of methane oxidation.